Diurnal variations of rainfall/attenuation - real time prediction of communication link performance - Wee, Juan Dee. (2008)
This thesis consists of 4 parts. There is a need to understand the impact of rain on the operations on satellite communication systems for both commercial and military application. Rain attenuation results in the reduction of time the satellite communication system is available for use. Satellite communication systems may be temporarily unavailable due to the loss of signal. The Ku band and the Ka band are more susceptible to rain fade which results in system outages especially in area where heavy rain fall are predominant.